Frugal innovation as a source of sustainable entrepreneurship to tackle social and environmental challenges - Muhammad Shehryar Shahid (7757021) (2023)
Sustainable entrepreneurs have increasingly faced challenges in achieving triple-bottom-line objectives. The study portrays frugal innovation as a source to foster sustainable entrepreneurship to move the debate beyond discussing the challenges of sustainable entrepreneurship. As such, we investigate how sustainable entrepreneurship with frugal innovation can tackle social and environmental challenges in the context of a developing country. An inductive approach with multiple case-method is used in this study. The results show that entrepreneurship based on frugal innovation leads to several social outcomes, such as female empowerment, improved quality of life, and access to affordable healthcare for low-income customers as well as environmental outcomes, such as sustainable products and production techniques. Furthermore, sustainable entrepreneurship creates new markets in developing countries and promotes inclusive growth. Our research reveals that sustainable entrepreneurship if based on frugal innovation, serves dual purposes. It enables businesses to make a profit and contribute to solving societal problems simultaneously. Juxtaposing with frugal innovation, we expand the field of sustainable entrepreneurship by shifting the debate from barriers to potential sources and enablers. Based on the findings, we provide implications and future research directions. Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclepro.2023.137050